The importance of pedagogy in the inclusion processes - Morgana Domênica Hattge; Viviane Klaus (Universidade Federal de Santa Maria (UFSM), 2014)
This paper initially attempts to problematize the inclusion processes established in education settings. The aim is to understand the meanings that the school inclusion has taken in the contemporary educational and academic scenario. By analyzing a number of researches that have focused on the production of the abnormal from clinical and psychological diagnoses and treatments, it is possible to notice the silence of Pedagogy, which is subject to the clinical or psy knowledge and ends up not playing its role in the production of pedagogical practices that meet the subjects' specific needs. Thus, the clinical diagnosis is regarded as absolute truth about the subject, and the interventions are often limited to medicalization. Therefore, it is fundamental to reflect on the relationships established between these different knowledges and their effects on the education settings. This paper invites us to reflect on the Pedagogy challenges in the construction of more inclusive processes in the education area.